Peran Serta Orang Tua dan Dampak Hospitalisasi pada Anak Usia 3-6 Tahun di Ruang Anak RSUD Poso - Nurfatimah Nurfatimah (Jurnal Bidan Cerdas, 2019)
Hospitalization is a process for reasons of planning or emergency that requires children to stay in the hospital to undergo therapy and treatment. The general objective of this tusy was to know the description of the participation of parents and the impact of hospitalization on children aged 3-6 years. This research used descriptive research method. The population in this study were all parents who have children aged 3-6 years who were treated in the Children's Room of Poso Regional Hospital as many as 48 children. The sampling technique was total sampling and the sample in this study were all parents who have children aged 3-6 years who are treated.. The statistical test used was the Chi-Square test. The results showed that 64.7% of respondents had a good role and 58.8% of respondents had children who were less affected by hospitalization. 77.3% of respondents who had good parents have children who were less affected by hospitalization. The conclusion of this study was the role of good parents can reduce the impact of hospitalization on children. This research suggests to reduce the impact of hospitalization on children, hospitals should create play programs for children so that children who are treated in hospitals do not feel bored while getting treatment.